1986
DOI: 10.1113/jphysiol.1986.sp016243
|View full text |Cite
|
Sign up to set email alerts
|

Human fixation and pursuit in normal and open‐loop conditions: effects of central and peripheral retinal targets.

Abstract: SUMMARY1. Eye movements were recorded precisely with a scleral-coil method under three experimental conditions: (a) fixation of a central, stationary target; (b) pursuit of a central, moving target; (c) pursuit of eccentric, moving targets. Subjects were instructed to attend to and fixate the target and to pursue it when it moved.2. The target was presented either in darkness (no visible background), on a diffusely lighted background, or on a large, structured background. Target and/or background could be move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…These results confirm those published previously (Barnes & Crombie, 1985;Murasugi et al, 1986). They also are consonant with the report that peripheral targets are pursued less well than central targets over a textured background (Collewijn & Tamminga, 1986). We conclude that when there are competing motion signals in different parts of the visual field, those motion signals that arise from objects nearest the fovea tend to dominate the oculomotor response.…”
Section: Effects Of Stationary Edges Alonesupporting
confidence: 82%
See 1 more Smart Citation
“…These results confirm those published previously (Barnes & Crombie, 1985;Murasugi et al, 1986). They also are consonant with the report that peripheral targets are pursued less well than central targets over a textured background (Collewijn & Tamminga, 1986). We conclude that when there are competing motion signals in different parts of the visual field, those motion signals that arise from objects nearest the fovea tend to dominate the oculomotor response.…”
Section: Effects Of Stationary Edges Alonesupporting
confidence: 82%
“…rubia (1983) reported a similar loss of gain at this velocity, but losses of up to about 20% for higher velocities. In a later paper, Collewijn and Tamminga (1986) reported that the ability to pursue targets 50 above and below the fovea was strongly degraded, even at low velocities, by the presence of a stationary structured background. In the present experiment, we were concerned with OKN; we were not interested in the limits to which voluntary pursuit may be pushed.…”
Section: Subjectsmentioning
confidence: 99%
“…However, the results of these studies are confusing and seem to be contradictory. The responses of subjects in some open-loop studies have been varied enough to lead the investigators to state that the use of this systems analysis technique is "useless" (18) and "unsuitable as a tool for analyzing the response characteristics of the smooth pursuit system" (5). Thus some investigators have expressed dissatisfaction with a technique that has potential value not only for the oculomotor systems but also for the analysis of other physiological control systems.…”
Section: Previous Open-loop Studiesmentioning
confidence: 99%
“…This is the same effect as if the feedback loop had been no matter how you move your eye, you cannot eliminate the cut, as in Fig tor may be the influence of prior experience on subject perforand the 1-sec mark, the subject made a series of saccades trying to mance. Examining the results from several studies (28,30,31) catch the target. When this strategy did not work, he seemed to turn reveals that open-loop gains are larger in subjects with more off the saccadic system and produce only smooth-pursuit eye moveexperience in laboratory tracking tasks.…”
Section: Opening the Loop On The Eye Movement Control Systemmentioning
confidence: 99%